Exudative Diabetic Maculopathy Treated By Frequancy Doubled Nd: Yag Laser (532nm) - AL Quriashi, Najah K. M. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Diabetic maculopathy means involvement of the macula by edema and exudates or ischemia which is the most common cause of visual impairment in diabetic patients, particularly those with type 2diabetes. Objective: The literatures are rich in publications of these regards, nevertheless the works in general were not systematic, not enough details regarding procedures and dose parameters in using laser for treatment are mentioned. "In the present work, an attempt to build a systematic procedure regarding dose parameters, application parameters and laser safety." Methods: A frequency doubled Nd: YAG laser was used to treat all eyes included in this study with diabetic maculopathy. Forty eyes of twenty five non insulin dependent diabetic Iraqi patients were evaluated, sixteen males and nine females. Their ages were 42- 76 years, all of them from patients attending ophthalmic out-patient department in the medical city. Results: Maculopathy regressed in 38/40 of the treated eyes, unchanged in 2/40 eyes and no one was deteriorated. Visual acuity improved in 6/40 of the treated eyes by at least two lines of Snellen’s chart while it stabilized in other 34/40. Conclusion: Exudative diabetic maculopathy is responsible for reduction in vision and even legal blindness in many patients. Close regular follow up and early laser treatment of eyes with maculopathy is significant in stabilization of vision and reducing the rate of visual loss.